Antibodies to Toxoplasma gondii, Leishmania spp., and Leptospira spp. in Free-ranging Six-banded Armadillos (Euphractus sexcinctus) from Northeastern Brazil - Barbosa, Werona de Oliveira; Coelho, Thiago Galvao; Costa, Talita Otaviano da; Paiz, Lais Moraes; Fornazari, Felipe [UNESP]; Langoni, Helio [UNESP]; Azevedo de Paula Antunes, Joao Marcelo; Alves Freitas, Carlos Ibere (Wildlife Disease Assoc, Inc, 2020)
Antibodies to pathogens of public health importance were investigated in 33 free-ranging six-banded armadillos (Euphractus sexcinctus) from Brazil. The frequency of seropositive animals for Toxoplasma gondii, Leishmania spp., and Leptospira spp. were two, three, and two, respectively.